Pola Komunikasi Pembinaan Santri Odgj Melalui Nilai-Nilai Islam Di Padepokan Tahfidhul Qur’an Ibnu Rusydi - Bani, Maulidan Al; Islam, Ahmad Fakhruddin Fajrul (Menara Tebuireng, 2024)
In this study, there are two problem formulations, namely: (1) What is the communication pattern of fostering students with ODGJ through Islamic values in Padepokan Tahfidhul Qur'an Ibn Rusydi? (2) What are the aspects that support and hinder the communication process in fostering ODGJ students in Padepokan Tahfidhul Qur'an Ibn Rusydi? To answer the two formulations of the problem. The researcher adopts a qualitative approach with a descriptive type in this study. The results of this study can be concluded that the communication pattern of ODGJ students at Padepokan Tahfidhul Qur'an Ibn Rusydi between caregivers, administrators, and ODGJ students uses verbal and nonverbal interactions to teach and provide an understanding of Islamic values to ODGJ students. That way, ODGJ students will be encouraged to think critically and adapt well in the social environment. Supporting factors such as an open attitude and active interaction accelerate the coaching process. Meanwhile, the inhibiting factors such as ODGJ students who have difficulty communicating can hinder the understanding and application of Islamic values. Effective social interaction is the key to achieving the vision and mission of making students noble individuals. Keyword: Communication Patterns, Santri, Mental Disorders, Islamic Values